2015
DOI: 10.1186/s12937-015-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 supplementation in HIV infection: effectiveness and associations with antiretroviral therapy

Abstract: BackgroundHIV infection and antiretroviral therapy (ART) may create unique risk factors for vitamin D insufficiency, including alterations of vitamin D metabolism by ART. We prospectively compared demographic and clinical parameters between vitamin D sufficient and insufficient HIV-infected (HIV+) adults, and assessed changes in these parameters among insufficient participants following standardized vitamin D supplementation.MethodsHIV+ adults (≥18 years old) with HIV-1 RNA <50 copies/mL on ART were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
0
30
1
Order By: Relevance
“…Although we have clearly demonstrated anti-infective and anti-inflammatory functions of vitamin D in mice, it is not known whether similar effects would occur in humans with PCP. It has been reported that 65% (63 of 97) of HIV-infected patients are deficient in vitamin D and that vitamin D supplementation for 24 weeks significantly increased the number of CD4 ϩ cells in these patients (54). This observation suggests that vitamin D supplementation would help resolve PCP in humans.…”
Section: Discussionmentioning
confidence: 88%
“…Although we have clearly demonstrated anti-infective and anti-inflammatory functions of vitamin D in mice, it is not known whether similar effects would occur in humans with PCP. It has been reported that 65% (63 of 97) of HIV-infected patients are deficient in vitamin D and that vitamin D supplementation for 24 weeks significantly increased the number of CD4 ϩ cells in these patients (54). This observation suggests that vitamin D supplementation would help resolve PCP in humans.…”
Section: Discussionmentioning
confidence: 88%
“…Coelho et al. reported that plasma 25(OH)D levels were significantly positively correlated with CD4 + T‐cell counts after 24 weeks of VitD supplementation and that each 1.0 ng/ml increase in 25(OH)D during repletion therapy was associated with a 3.3 cell/µl increase in the CD4 + T‐cell count . Although others have found that VitD supplementation is associated with reduced immune activation and CD4 + T‐cell exhaustion levels, it has no effect on CD4 + T‐cell recovery in both untreated and treated HIV‐1‐infected individuals .…”
Section: Intervention Measures For Poor Immune Reconstitutionmentioning
confidence: 99%
“…VDD is a common finding in HIV-infected patients. Coelho et al found that 63 out of 97 adult patients on antiretroviral therapy presented with insufficient levels of VD [ 72 ]. The investigators also showed that VD supplementation over 24 weeks improved CD4+ cell count recovery [ 72 ].…”
Section: Vitamin D and Human Immunodeficiency Virus Infectionmentioning
confidence: 99%